Ecological inference new methodological strategies - King, Gary 1958-; Rosen, Ori; Tanner, Martin Abba 1957- (Cambridge University Press, 2004)
Drawing upon the explosion of research in the field, a diverse group of scholars surveys strategies for solving ecological inference problems, the process of trying to infer individual behavior from aggregate data. The uncertainties and information lost in aggregation make ecological inference one of the most difficult areas of statistical inference, but these inferences are required in many academic fields, as well as by legislatures and the Courts in redistricting, marketing research by business, and policy analysis by governments. This wide-ranging collection of essays, first published in 2004, offers many important contributions to the study of ecological inference
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Sozialwissenschaften; Social sciences / Statistical methods; Political statistics; Inference; Umweltschutz; Statistik; Ökologie; Statistische Schlussweise; Aufsatzsammlung